Genetically Determined Later Puberty Impacts Lowered Bone Mineral Density in Childhood and Adulthood. (17th November 2017) - Cousminer, Diana L; Mitchell, Jonathan A; Chesi, Alessandra; Roy, Sani M; Kalkwarf, Heidi J; Lappe, Joan M; Gilsanz, Vicente; Oberfield, Sharon E; Shepherd, John A; Kelly, Andrea; McCormack, Shana E; Voight, Benjamin F; et al.
ABSTRACT: Later puberty associates with lower areal bone mineral density (aBMD), and both are risk factors for osteoporosis. However, the association between puberty timing–associated genetic variants and aBMD during development, and the causal relationship between puberty timing and aBMD, remain uncharacterized. We constructed sex‐specific polygenic risk scores (GRS) consisting of 333 genetic variants associated with later puberty in European‐descent children in the Bone Mineral Density in Childhood Study (BMDCS), consisting of a longitudinal cohort with up to seven assessments ( n  = 933) and a cross‐sectional cohort ( n  = 486). These GRS were tested for associations with age‐ and sex‐specific aBMD Z ‐scores at the lumbar spine (LS), femoral neck (FN), total hip, and distal radius, accounting for clinical covariates using sex‐stratified linear mixed models. The causal relationship between puberty timing and aBMD was tested in the BMDCS and in publicly available adult data (GEFOS consortium) using two‐sample Mendelian randomization (MR). The puberty‐delaying GRS was associated with later puberty and lower LS‐aBMD in the BMDCS in both sexes (combined beta ± SE = –0.078 ± 0.024; p  = 0.0010). In the MR framework, the puberty‐delaying genetic instrument also supported a causal association with lower LS‐aBMD and FN‐aBMD in adults of both sexes. Our results suggest that pubertal timing is causal for diminished aBMD in a skeletal site‐ and sex‐specific manner that tracks throughout life, potentially impacting later risk for osteoporosis, which should be tested in future studies. © 2017 American Society for Bone and Mineral Research.